Mitochondrial proteomics of the acetic acid – induced programmed cell death response in a highly tolerant Zygosaccharomyces bailii – derived hybrid strain - Joana F Guerreiro; Belém Sampaio-Marques; Renata Soares; Ana Varela Coelho; Cecília Leão; Paula Ludovico; Isabel Sá-Correia (Microbial Cell)
Very high concentrations of acetic acid at low pH induce programmed cell death (PCD) in both the experimental model Saccharomyces cerevisiae and in Zygosaccharomyces bailii, the latter being considered the most problematic acidic food spoilage yeast due to its remarkable intrinsic resistance to this food preservative. However, while the mechanisms underlying S. cerevisiae PCD induced by acetic acid have been previously examined, the corresponding molecular players remain largely unknown in Z. bailii. Also, the reason why acetic acid concentrations known to be necrotic for S. cerevisiae induce PCD with an apoptotic phenotype in Z. bailii remains to be elucidated. In this study, a 2-DE-based expression mitochondrial proteomic analysis was explored to obtain new insights into the mechanisms involved in PCD in the Z. bailii derived hybrid strain ISA1307. This allowed the quantitative assessment of expression of protein species derived from each of the parental strains, with special emphasis on the processes taking place in the mitochondria known to play a key role in acetic acid – induced PCD. A marked decrease in the content of proteins involved in mitochondrial metabolism, in particular, in respiratory metabolism (Cor1, Rip1, Lpd1, Lat1 and Pdb1), with a concomitant increase in the abundance of proteins involved in fermentation (Pdc1, Ald4, Dld3) was registered. Other differentially expressed identified proteins also suggest the involvement of the oxidative stress response, protein translation, amino acid and nucleotide metabolism, among other processes, in the PCD response. Overall, the results strengthen the emerging concept of the importance of metabolic regulation of yeast PCD.